AgWise Fertilizer Recommendation Module - Moltote, Feben Assefa; Degefie, Degefie Tibebe; Mkuhlani, Siyabusa; Ali Ibrahim; Ahmed, Jemal Seid; Devkota, Mina; Worku, Wuletawu Abera (2025)
The AgWise Fertilizer Recommendation Module generates site-specific nutrient and fertilizer recommendations for key crops and regions. The module provides users with three alternative modelling pathways, allowing flexibility depending on data availability, scale, and use case. Users may select any one of the three options to generate fertilizer recommendations (ML, ML+QUEFTS, ML+QUEFTS+Crop model).